Penerapan Media Kardus Pintar (SMART CARDBOARD) dalam Pembelajaran IPAS Materi Organ Pernapasan Manusia Kelas V MI Malik Ibrahim - Lina Agustin; Muhammad Suwignyo Prayogo; Nanda Riski Istikomah (Universitas Palan, 2025)
This research aims to explain how Smart Cardboard can be used to teach students in grade 5 Madrasah Ibtidaiyah about human respiratory health. Smart cardboard media is a visual and kinesthetic-based interactive learning tool that makes students' understanding of the anatomy and features of the human respiratory system easier. The classroom action research (PTK) was conducted with two cycles: planning, implementation, observation, and reflection. 19 Mi Malik Ibrahim 5th grade students were the research subjects. The results showed that the use of smart cardboard media can improve students' concept understanding, which is indicated by an increase in learning evaluation results from pre-action to post-action. It also increases students' participation in learning and makes the class more fun. Therefore, the smart cardboard media can be used successfully as an IPAS learning innovation that can improve students' learning outcomes and increase their interest in the lesson.